Telmisartan enhances mitochondrial activity and alters cellular functions in human coronary artery endothelial cells via AMP-activated protein kinase pathway. Issue 2 (April 2015) - Kurokawa, Hirofumi; Sugiyama, Seigo; Nozaki, Toshimitsu; Sugamura, Koichi; Toyama, Kensuke; Matsubara, Junichi; Fujisue, Koichiro; Ohba, Keisuke; Maeda, Hirofumi; Konishi, Masaaki; Akiyama, Eiichi; Sumida, Hitoshi; et al.
Abstract: Objective: Mitochondrial dysfunction plays an important role in cellular senescence and impaired function of vascular endothelium, resulted in cardiovascular diseases. Telmisartan is a unique angiotensin II type I receptor blocker that has been shown to prevent cardiovascular events in high risk patients. AMP-activated protein kinase (AMPK) plays a critical role in mitochondrial biogenesis and endothelial function. This study assessed whether telmisartan enhances mitochondrial function and alters cellular functions via AMPK in human coronary artery endothelial cells (HCAECs). Methods and results: In cultured HCAECs, telmisartan significantly enhanced mitochondrial activity assessed by mitochondrial reductase activity and intracellular ATP production and increased the expression of mitochondria related genes. Telmisartan prevented cellular senescence and exhibited the anti-apoptotic and pro-angiogenic properties. The expression of genes related anti-oxidant and pro-angiogenic properties were increased by telmisartan. Telmisartan increased endothelial NO synthase and AMPK phosphorylation. Peroxisome proliferator-activated receptor gamma signaling was not involved in telmisartan-induced improvement of mitochondrial function. All of these effects were abolished by inhibition of AMPK. Conclusions: Telmisartan enhanced mitochondrial activity and exhibited anti-senescence effects and improving endothelial function through AMPK in HCAECs. Telmisartan could provide beneficial effects on vascular diseases via enhancement of mitochondrial activity and modulating endothelial function through AMPK activation. Highlights: Telmisartan enhanced mitochondrial activity. Telmisartan improved endothelial function. AMPK plays a key role on telmisartan-induced mitochondrial activation.